Evaluasi User Experience Website E-Learning My-Elnusa Menggunakan User Experience Questionnaire (UEQ) - Sabam Yehezkiel Ricardo Marpaung; Nia Nuraeni (Universitas Bina Sarana Informatika Kota Sukabumi, 2023)
Nusa Mandiri University has an e-learning service called MyE-Learning System Nusa Mandiri (MyELNUSA), but the system has not been evaluated on the user experience aspect. User experience includes the impressions and emotions of users when using a product and when the product can provide an efficient and pleasant service, the product can be stated positively on the user experience. In this MyELNUSA application, it is necessary to know how far the user experience measure is to the user. User Experience Questionnaire (UEQ) as an evaluation method consisting of six rating scales, namely attractiveness, perspicuity, efficiency, dependability, stimulation, and novelty. In this method there are 26 question items in the form of 2 attributes that are paired with opposite meanings. This evaluation is important because it is useful in knowing the user experience of the application and providing suggestions for improvements needed. Tests were carried out on 34 active students who used the MyELNUSA application and the results obtained that in the efficiency and aura aspects got scores above the average and then in the attractiveness, clarity, accuracy, and stimulation aspects they got below average scores. The recommended areas for improvement are aspects of attractiveness, clarity, accuracy and stimulation